The effect of standard heat and filtration processing procedures on antimicrobial activity and hydrogen peroxide levels in honey - Chen, Cuilan; Campbell, Leona; Blair, Shona E.; Carter, Dee A. (Frontiers in Microbiology, 2012)
There is increasing interest in the antimicrobial properties of honey. In most honey samples, antimicrobial activity is due to the generation of hydrogen peroxide (H2O2) by the bee-derived enzyme glucose oxidase, however the amount of H2O2 produced can vary greatly among samples. In addition, honey is a complex product, and other components may contribute to or modulate this activity, which may be further affected by processing procedures used in large-scale commercial production. In this study we examined honey derived from three native Australian floral sources that had previously been associated with H2O2-dependent activity: spotted gum (Eucalyptus maculata), red stringybark (Eucalyptus macrorrhyncha) and yellowbox (Eucalyptus melliodora). Antimicrobial activity was measured using standardized assays against the bacterial pathogen Staphylococcus aureus and the fungal pathogen Candida albicans. Antibacterial activity was only seen in four of the six red stringybark samples and ranged from 12-21.1% phenol equivalence. No antibacterial activity was detected in the spotted gum or yellowbox samples. Antifungal activity ranged from MIC values of 19-38.3 % (w/v), and although all samples were significantly more active than an osmotically equivalent sugar solution, most had relatively low activity. All honey samples were provided unprocessed and underwent standard heating and filtration procedures (45˚C for 8 hours followed by filtration with a 100 µm filter), allowing the effects of commercial heating and filtration methods on antimicrobial activity and H2O2 levels to be assessed. Average antibacterial and antifungal activities decreased, but while processing was usually detrimental, occasionally the reverse was seen and antimicrobial activity increased. Significant activity was eliminated from all samples by the addition of catalase, indicating that H2O2 was chiefly responsible for their antimicrobial action, and H2O2 production was measured in the honey samples using